Relation between burden of disease and randomised evidence in sub-Saharan Africa: survey of research - Isaakidis, Petros; Swingler, George H; Pienaar, Elizabeth; Volmink, Jimmy; Ioannidis, John P A (BMJ, 2002)
Abstract Objective: To evaluate whether the amount of randomised clinical research on various medical conditions is related to the burden of disease and health needs of the local populations in sub-Saharan Africa. Design: Construction and analysis of comprehensive database of randomised controlled trials in sub-Saharan Africa based on Medline, the Cochrane Controlled Trials Register, and several African databases. Setting: Sub-Saharan Africa. Main outcome measures: Number of trials and randomised subjects for each category of disease in the global burden of disease taxonomy; ratios of disability adjusted life years (DALYs) per amount of randomised evidence. Results: 1179 eligible randomised controlled trials were identified. The number of trials published each year increased over time. Almost half of the trials (n=565) had been done in South Africa. There was relatively good correlation between the estimated burden of disease at year 2000 and the number of trials performed (r=0.53, P=0.024) and the number of participants randomised (r=0.68, P=0.002). However,some conditions—for example, injuries (over 20 000 DALYs per patient ever randomised)—were more neglected than others. Conclusion: Despite recent improvements, few clinical trials are done in sub-Saharan Africa. Clinical research in this part of the world should focus more evenly on the major contributors to burden of disease. What is already known on this topic Sub-Saharan Africa has a large burden of disease Little clinical research is conducted for problems affecting sub-Saharan Africa What this study adds Only 1179 randomised controlled trials conducted in sub-Saharan Africa in the past 50 years were identified Correlation between the amount of randomised evidence and the estimated burden of disease was fairly good However, some disease categories were more neglected than others, with the worst being injuries